Multimodal Antibacterial Platform Constructed by the Schottky Junction of Curcumin‐Based Bio Metal–Organic Frameworks and Ti3C2Tx MXene Nanosheets for Efficient Wound Healing. Issue 10 (14th September 2022) - Guo, Chuanpan; Cheng, Fang; Liang, Gaolei; Zhang, Shuai; Duan, Shuxia; Fu, Yingkun; Marchetti, Fabio; Zhang, Zhihong; Du, Miao
Abstract : A novel multimodal antibacterial platform is constructed by the in situ growth of a bioactive zinc‐based metal–organic framework (Zn‐MOF) using the natural antibacterial agent (curcumin) as ligand over the Ti3 C2 T x nanosheets (NSs) for highly effective bacteria‐infected wound healing. As Zn nodes in Zn‐MOF can be partially exchanged by Ti sites in Ti3 C2 T x NSs, a novel oxygen vacancy‐rich Schottky junction is formed at the interface between Zn‐MOF and Ti3 C2 T x NSs, which can remarkably improve the separation and electron transfer efficiency of photoinduced carriers under near‐infrared light irradiation (808 nm). Consequently, it affords the Zn‐MOF@Ti3 C2 T x Schottky junction abundant superoxide radicals (O2 − ) and hydroxyl radicals (OH) by electron transfer via type I mechanism and singlet oxygen ( 1 O2 ) by energy transfer via type II mechanism, accompanying the superior photothermal performance and controllable release of Zn 2+ ions and curcumin. The Zn‐MOF@Ti3 C2 T x shows excellent biocompatibility and multimodal antibacterial ability toward Staphylococcus aureus and Escherichia coli . Based on the detailed investigations of the antibacterial mechanism, the Zn‐MOF@Ti3 C2 T x Schottky junction remarkably demonstrates accelerated wound healing (wound closure ratio is >99%) infected by S. aureus . Abstract : A multimodal antibacterial platform based on a novel Schottky barrier junction is designed and constructed for bacterium‐infected wound healing via the synergistic antibacterial mechanism of PTT/PDT and release of metal ions and antibiotics. The Zn‐metal–organic framework (MOF)@Ti3 C2 T x can efficiently reduce the needed dosage of antibacterial agent, affording excellent healing ability, low biotoxicity, and enhanced wound healing effect.